SECOND REPORT OF THE OCCURRENCE OF GIANT TIGER PRAWN, Penaeus monodon FABRICIUS, 1798 (CRUSTACEA: DECAPODA), IN RIO GRANDE DO NORTE STATE, NORTHEAST BRAZIL - Junior, Edivan Morais de Souza; Júnior, José Garcia; Araújo, Paulo Victor do Nascimento; Alencar, Carlos Eduardo Rocha Duarte; Freire, Fúlvio Aurélio de Morais (Arquivos de Ciências do Mar, 2015)
In April 2012, a specimen of giant tiger prawn, Penaeus monodon , was captured by an artisanal bottom trawlboat on the northern continental shelf of Rio Grande do Norte State, northeastern Brazil. This specimen, a female, was collected from a 4-meter depth, had a partial total length of 249.6 mm and weighted 173 g. This is the second report of P. monodon off the coast of Rio Grande do Norte, 11 years after the first record, which suggests an ongoing southward expansion of this species in northeastern Brazil.